Multiple Aspects of Chronic Diseases in the Americas - Cotelea, Svetlana (My University, 2011)
The purpose of the reported internship program was to gain insight into the realities of working in the field of Public Health at a large organization level. The focus of the program was to study multiple aspects of chronic diseases in populations, and strategies to reduce their burden. In the 21st century, non-communicable diseases shape epidemiological profiles of many countries in the Americas. Of particular concern is the increasing overlapping of communicable and non-communicable diseases. Diabetes and tuberculosis co-morbidity is a particular example of this new epidemiological pattern. The association between diabetes prevalence and the incidence of tuberculosis is reported here. I helped conduct an ecologic analysis for the 26 countries from the Americas. Diabetes was found to be associated with tuberculosis burden in the Americas, with 16.5% of all incident cases of tuberculosis attributed to diabetes. Collaborative initiatives between tuberculosis and diabetes control services are needed. Essential components of the comprehensive management of chronic diseases at the population level are: 1) good quality health data and documentation of trends, 2) educational programs for patients to develop their self-monitoring abilities, 3) regular medical care and evaluation of associated risk factors and complications, 4) relevant research exploring new features, and 5) identification of the most cost-effective strategies and economically-realistic solutions. During my 2010 internship program at the Pan American Health Organization, I touched upon each of these components through: 1) preparing a summary of data for the last three years on chronic conditions in general, and diabetes in particular, in countries of the Americas to contribute to the next edition of Health in the Americas; 2) preparing the introduction for the second edition of Atlas of Diabetes Education in Latin America and the Caribbean; 3) providing input from a clinical perspective regarding information included in the Chronic Care Passport and its supplementary booklet for health care providers; 4) contributing to the grant writing for a proposal entitled Addressing the burdens of diabetes and tuberculosis in the Americas; and 5) preparing an inventory of studies on health economic evaluations that addressed chronic diseases in the Americas.
Keywords: Nutrition; Public Health; Diabetes; Tuberculosis; Pan American Health Organization; PAHO; Public Health (0573)